2003
DOI: 10.1029/2002jd003112
|View full text |Cite
|
Sign up to set email alerts
|

New particle formation in anthropogenic plumes advecting from Asia observed during TRACE‐P

Abstract: The characteristics and sources of what are believed to be newly formed 3 to 4 nm particles in anthropogenic plumes advecting from Asian are reported. Airborne measurements were made from March to April 2001 as part of the NASA TRACE‐P experiment at latitudes ranging from North of the Philippines to Northern Japan (20 to 45°N). In the more polluted plumes, high concentrations of 3 to 4 nm diameter particles (>100cm−3) were observed both within and along the upper outer edges of plumes that were identified by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 48 publications
5
58
0
Order By: Relevance
“…It should be noted that, while S 0 in polluted regions is quite large, the concentration of precursor gases can be very high as well. (Weber et al, 2003). Table 2 gives the steady state ion-mediated nucleation rates at the critical size (J crit ) and at 3 nm (J 3 nm , i.e., the "apparent" formation rates as observed) under a number of different combinations of sulfuric acid concentration and surface area of preexisting particles.…”
Section: Simulations and Comparisons With Observationsmentioning
confidence: 99%
“…It should be noted that, while S 0 in polluted regions is quite large, the concentration of precursor gases can be very high as well. (Weber et al, 2003). Table 2 gives the steady state ion-mediated nucleation rates at the critical size (J crit ) and at 3 nm (J 3 nm , i.e., the "apparent" formation rates as observed) under a number of different combinations of sulfuric acid concentration and surface area of preexisting particles.…”
Section: Simulations and Comparisons With Observationsmentioning
confidence: 99%
“…Therefore, securing aerosol data sets of global coverage is important, especially with regard to the number concentration, which is of primary concern when it comes to cloud and aerosol interaction because the number of cloud droplets is initially determined by the number of aerosol particles that can be activated as embryonic cloud droplets at a given supersaturation (S). Such information is relatively scarce in East Asia compared to Europe and North America (Kumala et al, 2004), although various efforts have been made in recent years, including those that tried to characterize new particle formation (Weber et al, 2003;McNaughton et al, 2004;Wu et al, 2007;Lee et al, 2008;Park et al, 2008;Wiedensohler et al, 2009;Song et al, 2010;Kim et al, 2012Kim et al, , 2013 and CCN properties (Matsumoto et al, 1997;Adhikari et al, 2005;Yum et al, , 2007; J. H. Mochida et al, 2010;Rose et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Clement et al, 2002b) have shown that a large AP surface area will suppress nucleation events, if the SO 2 concentration is less than a specific value, due to the competing mechanisms of gas-phase nucleation and coagulation scavenging to pre-existing AP. In a plume with large AP surface area such as this, Weber et al (2003) indicated that new particle formation would proceed if the SO 2 concentration was above about 2 ppbv (the measured SO 2 concentration was about 0.5 ppbv). However, recent calculations by Kulmala et al (2006a) have shown that only a minimal amount of SO 2 may be required for the formation of 3 nm (diameter) particles via cluster activation, as opposed to classical binary homogeneous nucleation.…”
Section: Horizontal Profilesmentioning
confidence: 99%
“…Identification of regions of new particle formation by high concentrations of UCN is arbitrary and we have only included the obvious peak in UCN. For example, Weber et al (2003) considered areas of new particle formation to be regions where the UCN concentration exceeded 100 cm −3 which, if applied here, would extend the region of new particle formation to 1 km asl. Accumulation mode AP, as measured by the ASASP, had a maximum concentration of about 900 cm −3 and surface area 150 µm 2 cm −3 .…”
Section: Horizontal Profilesmentioning
confidence: 99%